2021
DOI: 10.1007/s11187-021-00464-x
|View full text |Cite
|
Sign up to set email alerts
|

Who benefits from SMEs’ radical innovations?—empirical evidence from German biotechnology

Abstract: We analyze transfer channels of radical innovations launched by small and medium-sized firms (SMEs) using an ego network approach. Based on a unique longitudinal dataset covering the observation period 1996–2016, we identify and trace back radical innovations of SMEs in German Biotech in order to analyze the extent to which SMEs themselves—or eventually also other organizations in their direct cooperation surrounding—benefit from radical innovations in terms of subsequent innovation performance. Results from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 87 publications
1
18
0
Order By: Relevance
“…3 shows that a size effect can be observed that follows the presumed path of general patent activity across different firm sizes. To address this issue, similar to Shkolnykova & Kudic (2021), we identified statistical twins that are very similar, in a statistical sense, to firms with AI patents, but do not have AI patents themselves. In more concrete terms, we matched each firm that had at least one AI patent in a specific year with one other non-AI patenting firm, starting with the year 2011, where a firm is matched if it has its first AI patent in the dataset 1 year later (2012 in this instance).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 shows that a size effect can be observed that follows the presumed path of general patent activity across different firm sizes. To address this issue, similar to Shkolnykova & Kudic (2021), we identified statistical twins that are very similar, in a statistical sense, to firms with AI patents, but do not have AI patents themselves. In more concrete terms, we matched each firm that had at least one AI patent in a specific year with one other non-AI patenting firm, starting with the year 2011, where a firm is matched if it has its first AI patent in the dataset 1 year later (2012 in this instance).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, radical innovations hold the potential for strong competitive advantages (Castaldi et al, 2015) and future sustainable economic growth (Ahuja & Lampert, 2001;Arthur, 2007). Since there is still no universal definition of radical innovations in the literature (Shkolnykova & Kudic, 2021), they have also been framed as "technological breakthroughs" (Castaldi et al, 2015), "disruptive innovations" (Tushman & Anderson, 1986) or "atypical innovations" (Uzzi et al, 2013). However, following recent approaches (e.g.…”
Section: Theoretical Background: Radical Innovation Ai and Firm Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the difference in the technological and scientific knowledge between companies is an important factor in the process of technical change and in constructing the necessary capabilities for R&D (Hagedoorn & Duyster, 2002;Makri et al, 2010). In a recent study Shkolnykova and Kudic (2021) found that in biotechnology, partner firms that focus on different technological fields can benefit more from the other companies' radical innovation than firms that focus on the same area. This conclusion increases the importance of existing differences in the firms' knowledge bases.…”
Section: The Impact Of the Knowledge Base On Technological Developmentmentioning
confidence: 99%
“…Researchers have regarded collaboration as an important mechanism that can improve the competitiveness of enterprises or areas (Cumming et al, 2014). Not only radically innovating small and medium-sized enterprises themselves but also various types of directly linked cooperation partners benefit significantly from direct cooperation (Shkolnykova & Kudic, 2021). However, to date, little importance has been attached to blockchain technology collaboration in developing and developed countries.…”
Section: Introductionmentioning
confidence: 99%